Peranan Pendidikan Agama Islam Dilingkungan Sekolah Terhadap Sikap Bertoleransi Berbeda Agama Di SD Negeri 08 Kepahiang - Enik Maulia; M Taqiyuddin (Yayasan Darusssalam Bengkulu, 2025)
This study aims to determine the role of Islamic religious education in the school environment towards attitudes of tolerance of different religions in SD Negeri 08 Kabawetan. Data and data sources for this type of survey data collection are divided into primary and secondary data types. Primary data is data taken directly from a location (from a source) and needs to be analyzed further. Data collection techniques in this study, the author uses several methods of collecting interview and observation data. This study uses a qualitative descriptive method. This study was conducted at SD Negeri 08 Kabawetan. The results of this study indicate that students of SD Negeri 08 Kabawetan have a fairly high attitude of tolerance.